Problematika Pembelajaran Daring Masa Pandemi Covid-19: Indonesia - Asridayati Asridayanti; Rita Sari (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2021)
During the Covid-19 outbreak spread globally, learning in schools is also done online or online. Thisis to reduce the spread of the corona virus among students. The purpose of this study analyzesvarious problems and online learning that takes place today during the Covid-19 pandemic in termsof teachers, student side and parent side. This type of research is qualitative. The study subjects werenine people consisting of three teachers, three students and three parents of students. The datacollection techniques in this study are interviews and documentation. The data analysis techniques inthis study consist of data reduction, data presentation and conclusion withdrawal. The results of thisstudy are online learning problems that are reviewed from the teacher's side, namely the limitedability of IT teachers in using various applications such as Zoom, Google meet and google classroomin the online learning process. While the problem experienced by students is the need for internetquotas that are considered expensive, the material is felt difficult and not understood by students andstudents are not focused on learning. While the obstacle of parents is the concern about the child'slearning interest during online learning is greatly decreased, children are lazier to learn andchildren's morals are also getting worse.